Analysis of organic pollutants in water samples of White Drin, Black Drin and Fierza Reservoir - Aurel Nuro; Elda Marku; Bledar Murtaj (Journal of Engineering & Processing Management, 2017)
This study presented data about concentrations of some organic pollutants inAlbanian part of Black Drin (BD), White Drin (WD) and Fierza Reservoir (FR).Thirteen stations were analyzed in this study. Sampling of water was realized inMay 2017. Drin River presents important aquatic area in Albania. For all watersamples were analyzed organochlorine pesticides (OCPs), polychlorinatedbiphenyls (PCBs), benzene, toluene, ethylbenzene and o-, m-, p-xylenes (BTEX)and polyromantic hydrocarbons (PAH). Organochlorined pesticides and PCBswere found in higher level for Fierza Reservoir stations. Their concentrations forBlack and White Drin samples were 5-10 times lower.
Keywords: Drin River; GC/ECD/FID; Fierza Reservoir; Organic pollutants; water samples